A Case with Hematological Abnormality Characterized by the Absence of Peroxidase Activity in Blood Polymorphonuclear Leukocytes - Katsuyama, Nobuo; Satodate, Ryoichi; Higashi, Ototaka (The Tohoku Journal of Experimental Medicine, 1965)
A case with quite an unusual hematological abnormality characterized by the absence of peroxidase activity in the majority of polymorphonuclears and monocytes in blood was reported. This abnormality in the present patient was associated both with a megaloblastic anemia which was refractory to folic acid or vitamin B12 and also with a relatively mild proliferation of immature leuko-cytes in the bone marrow. The latter feature above all made us hesitate to diagnose the case as one kind of leukemic disease.